2014
DOI: 10.1007/s10096-014-2049-3
|View full text |Cite
|
Sign up to set email alerts
|

Increasing use of third-generation cephalosporins for pneumonia in the emergency department: may some prescriptions be avoided?

Abstract: Third-generation cephalosporins are used to treat inpatients with community-acquired pneumonia. Some of these prescriptions may be avoided, i.e. replaced by agents less likely to promote ESBL-mediated resistance. Our objectives were to assess the recent trend of third-generation cephalosporins use for pneumonia in the emergency department, and the proportion of avoidable prescriptions. This was a retrospective study of patients treated for community-acquired pneumonia in an emergency department, and subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…It is important to note that conversely to French recommendations, amoxicillin/beta-lactamase inhibitor is proposed as a possible first-line empirical beta-lactam for ICU patients with CAP in North American [11] and British [25] guidelines. Reducing the use of third-generation cephalosporins for CAP is already suggested in the emergency department [26]. …”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that conversely to French recommendations, amoxicillin/beta-lactamase inhibitor is proposed as a possible first-line empirical beta-lactam for ICU patients with CAP in North American [11] and British [25] guidelines. Reducing the use of third-generation cephalosporins for CAP is already suggested in the emergency department [26]. …”
Section: Discussionmentioning
confidence: 99%
“…The first study population originated from a French academic centre (Centre Hospitalier Universitaire de Nantes, Nantes, France), the study period ranging from January 2002 to December 2015. Patients who were hospitalized between 2002 and 2013 have been described previously [5,20]. The second study population originated from a previously reported multicentre study in seven other French hospitals, including two academic centres [5].…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
“…In order to cover both community-acquired and healthcare-associated pneumonia and to exclude hospital-acquired pneumonia, patients transferred from another acute-care hospital to the ED were not eligible. Among eligible patients, we randomly selected 100 cases per year (except for 168 cases in 2013) using a computer-generated random number list [5,20]. Among these randomly selected cases, inclusion and exclusion criteria were subsequently applied.…”
Section: Study Design Setting and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Par ailleurs, la proportion de traitement par C3G injectable a fortement augmenté entre 2002 et 2012, et il existe une forte variation de la proportion de patients traités par C3G et/ou FQ entre structures d'urgences, indépendamment de la gravité des patients [9,10]. Ces constats concordants indiquent qu'il existe une surprescription de C3G, et dans une moindre mesure de FQ dans les infections respiratoires basses traitées aux urgences.…”
Section: Mots Clés Céphalosporines · Fluoroquinolones · Bon Usage Desunclassified